2018
DOI: 10.1111/petr.13249
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival outcome between donor types or stem cell sources for childhood acute myeloid leukemia after allogenic hematopoietic stem cell transplantation: A multicenter retrospective study of Study Alliance of Yeungnam Pediatric Hematology‐oncology

Abstract: We compared transplant outcomes between donor types and stem cell sources for childhood acute myeloid leukemia (AML). The medical records of children with AML in the Yeungnam region of Korea from January 2000 to June 2017 were reviewed. In all, 76 children with AML (male-to-female ratio = 46:30) received allogenic hematopoietic stem cell transplantation (allo-HSCT). In total, 29 patients received HSCT from either a matched-related donor or a mismatched-related donor, 32 patients received an unrelated donor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This has also been reported in children receiving T-replete CBT for myeloid malignancy with an increased rate of TRM compared to a comparator arm (hazard ratio 2.04; p = 0.042) (3). Other studies, however, have produced conflicting data with no significant increase in TRM detected with CBT (38,40,[45][46][47][48]. Heterogeneity of patient populations, disease groups, conditioning regimens, particularly the use of T-depleting serotherapy and outcome measures confounds direct comparison of these studies.…”
Section: Transplant-related Mortality Including Infectious Complicationsmentioning
confidence: 71%
“…This has also been reported in children receiving T-replete CBT for myeloid malignancy with an increased rate of TRM compared to a comparator arm (hazard ratio 2.04; p = 0.042) (3). Other studies, however, have produced conflicting data with no significant increase in TRM detected with CBT (38,40,[45][46][47][48]. Heterogeneity of patient populations, disease groups, conditioning regimens, particularly the use of T-depleting serotherapy and outcome measures confounds direct comparison of these studies.…”
Section: Transplant-related Mortality Including Infectious Complicationsmentioning
confidence: 71%
“…According to the cytogenetics data, the survival outcome of chemotherapy and HSCT did not show any significant difference. In addition, in a previous study, we had reported that there is no difference in the survival outcome based on donor type and stem cell source after allogenic HSCT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the many patients who lack a suitable HLA (human leukocyte antigen)-matched donor, the use of alternative donors—i.e., mismatched unrelated donors, unrelated cord blood (CB) donors, and haplo-identical family donors—has extended the possibility of hematopoietic stem cell transplantation (HSCT) 1 . The use of CB has some major advantages: it can be more readily available; it tolerates some degree of HLA mismatch, which greatly helps in finding suitable CB units; and it yields a reduced risk of graft-versus-host disease (GvHD) and relapse 2 .…”
Section: Introductionmentioning
confidence: 99%